Segmentation Analysis of Consumer Expenditures in Home Appliances Products - Michael; Helga Meilany; Aditya Rachman Zarkasih; Jerry Heikal (LPPM STIE EKA PRASETYA, 2024)
The digital era has brought significant changes in the way consumers view and purchase household appliances. Technological advances, lifestyle changes and emerging market trends have all played a role in shaping consumer spending habits in this sector. This research aims to determine the segmentation of consumer spending in shopping for home appliances products. The method used is descriptive quantitative k-mean clustering in SPSS software based on the results of a random sampling survey of 100 samples from 10.000 population. Based on research results, it shows that cluster 5 with persona SpendThrift Families is the best target cluster for home appliances companies to sell their products, especially in the categories of gardening equipment, kitchen appliances, and bathroom & laundry.